Indigenous knowledge associated with the production of starters culture used to produce Beninese opaque sorghum beers - N'TCHA, C; ADEYEMI, A.D.; KAYODE, Adéchola P. P.; VIEIRA-DALODE, Générose; AGBOBATINKPO, B.P.; CODJA, J.T.C.; BABA-MOUSSA, LAMINE (My University, 2015)
Objective: The present study aims to document the indigenous Knowledge associated with the production of starters culture to be used for opaque sorghum beers manufacturing in Benin Methodology and results: A quantitative survey was carried out in the central and the northern regions of Benin. A total of ninety (90) processors of traditional beers were interviewed using a semi-structured questionnaire. The collected information was related to the processing method of the starters’ production, its shelf life as well as sociodemographic data on the producers. Five types of starters were identified during this investigation. Apart from the beer itself which can be used as starter, we can distinguish kpètè-kpètè; the fermentation calabash, the bag and the belt of fermentation. Among them, the fermentation calabash was mostly used by 74% (67/90) of beer producers followed by kpètè-kpètè 21% (19/90). In some cases, these starters were used in association with each other to speed up the fermentation process. All the producers were women with an average age of 38 years old. Among those women, about 73% (66/90) produce and sell the beer as principal activity. According to 56% (51/90) of the producers, the quality of the manufactured beer depends on the quality of the starter used. Many other factors such as the sorghum variety, the brewing technique can also affect the beer quality. It is reported by 70% (63/90) of producers that the storage duration reduces the fermentative ability of kpètè-kpètè. Some health-related properties such as the treatment of diarrhoea have been attributed to kpètè-kpètè by 73% (66/90) of the producers interviewed. Conclusion and application of results: the fermentation calabash is the most used starter by traditional beer producers because of the quality of the derived beer. The kpètè-kpètè comes in the second position but possesses the advantage of being used by people to cure humans and animals diseases. Further investigations are needed to identify the functional microorganisms involved in the kpètè-kpètè to better understanding its health-related attributes.
Keywords: Indigenous Knowledge; tchoukoutou; kpètè-kpètè; fermentation; Benin